Modeling Carbon Emissions and Energy Transition in the Context of Indonesia’s Economic Expansion - Darmayanti, Novi; Sutisman, Entar; Nurhayati, Nurhayati; Ratnasari, Sri Langgeng; Suryani, Arna; Fahlevi, Mochammad (International Journal of Energy Economics and Policy, 2025)
This study looks at how economic growth, renewable energy use, and carbon dioxide emissions interact in Indonesia’s energy plans. It uses data from 1990 to 2023 and a method called ARDL bounds testing to study both long-term and short-term changes in these areas. The results show that economic growth increases CO2 emissions, but using renewable energy helps reduce this effect. This highlights the importance of renewables for low-carbon growth. The study also finds that CO2 emissions lead to more renewable energy use, suggesting that environmental concerns, not just economic growth, influence energy policies in Indonesia. These findings support the idea that as economies grow, they can become more environmentally friendly. However, Indonesia’s current efforts to cut emissions may not be enough to meet climate goals due to infrastructure and policy challenges. This study suggests the need for new policies, better energy grids, stronger accounting-based transparency in carbon markets, and cooperation between public and private sectors to speed up the shift to sustainable energy. Indonesia’s experience offers important lessons for other developing countries trying to balance economic growth with environmental care.